Thor's wedding day : by Thialfi, the goat boy - Coville, Bruce; Cogswell, Matthew (Orlando, Fla. : Harcourt, 2005)
Thialfi, the Norse thunder god's goat boy, tells how he inadvertently helped the giant Thrym to steal Thor's magic hammer, the lengths to which Thor must go to retrieve it, and his own assistance along the way.
Bulletin (Center for Children's books)
Horn Book
Wilson's Junior High School
6.2
3-6.
3-6
Keywords: Giants -- Fiction; Goats -- Fiction; Hammers -- Fiction; Loki (Norse deity) -- Fiction; Mythology, Norse -- Fiction; Thor (Norse deity) -- Fiction; Giants -- Fiction; Goats -- Fiction; Hammers -- Fiction; Loki (Norse deity) -- Fiction; Norse mythology -- Fiction; Thor (Norse deity) -- Fiction